2021
DOI: 10.1080/16549716.2021.1965305
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperatures and cardiovascular mortality: assessing effect modification by subgroups in Ganzhou, China

Abstract: Background Many people die from cardiovascular diseases each year, and extreme temperatures are regarded as a risk factor for cardiovascular deaths. However, the relationship between temperature and cardiovascular deaths varies in different regions because of population density, demographic inequality, and economic situation, and the evidence in Ganzhou, China is limited and inconclusive. Objective This study aimed to assess extreme temperature-related cardiovascular mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We postulated several possible explanations for this phenomenon. Overall, age is a common risk factor for CVD mortality with older people, especially women, being more susceptible [13,[47][48][49][50]. Most women over the age of 50 years have undergone menopausal transition, which has long been associated with decreased cardio-protection and an increase in the risk of developing CVDs and vulnerability to heat [51].…”
Section: Discussionmentioning
confidence: 99%
“…We postulated several possible explanations for this phenomenon. Overall, age is a common risk factor for CVD mortality with older people, especially women, being more susceptible [13,[47][48][49][50]. Most women over the age of 50 years have undergone menopausal transition, which has long been associated with decreased cardio-protection and an increase in the risk of developing CVDs and vulnerability to heat [51].…”
Section: Discussionmentioning
confidence: 99%
“…We postulated several possible explanations for this phenomenon. Overall, age is a common risk factor for CVD mortality with older people, especially women, being more susceptible [13,[44][45][46][47]. Most women over the age of 50 years have undergone menopausal transition, which has long been associated with decreased cardio-protection and an increase in the risk of developing CVDs and vulnerability to heat [48].…”
Section: Discussionmentioning
confidence: 99%
“…More than half (54%) of patients died within 48 hours of being admitted to the hospital. No 1784 (45) The mean dry bulb temperature and humidity for Puducherry was around 29 o C and 76%, respectively. The mean T app , which takes both of these into account along with VP and WS was slightly higher in Puducherry between 2010 and 2020, around 33 o C. Two thirds of the patients were older than 60 years (65.2%).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Interestingly, we did not find evidence for consistent effect modification by sex (stronger effects of the air temperature on eight biomarkers in men and five biomarkers in women). Several previous studies found that the mortality among men exposed to low temperatures was higher than that among women, while other studies showed opposite findings. , Overall, the role of sex in modifying temperature–mortality associations is not clear, which could at least partly be due to differential effects of air temperature on different biomarkers of subclinical inflammation that vary according to sex.…”
Section: Resultsmentioning
confidence: 91%